Design pistole na laser game - Krakovský, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2014)
Předmětem této bakalářské práce je design pistole na laser game. Cílem je vytvořit funkční návrh futuristické zbraně respektující technické, ergonomické a estetické požadavky.

The main subject of this bachelor thesis is to design the laser game gun. The goal of the design is to create a functional concept of futuristic gun respecting technical, ergonomic and aesthetic requirements.
Design of laser game gun
Keywords: Laser game; pistole; design; ergonomie; Laser game; gun; design; ergonomics